PENGARUH PENDIDIKAN KESEHATAN BERBASIS AUDIOVISUAL TERHADAP PENGETAHUAN IMS PADA REMAJA DI KABUPATEN SELUMA - Nimas Ayu Lestari Nurjanah (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2025)
Sexually transmitted infections (IMS) refer to diseases commonly spread through sexual activity. Fungi, viruses, and parasites are some of the microorganisms that can cause infections. Currently, adolescents are more susceptible to sexually transmitted infections. According to the Indonesian Ministry of Health, in 2022, there were 19,973 IMS cases in Indonesia, showing an increasing trend. One factor contributing to the increase in sexually transmitted infections among adolescents is a lack of knowledge about these diseases. To increase adolescents' knowledge, learning media that can illustrate physical concepts are needed. Audiovisual media is one such medium. This study aims to determine the effect of health education using audiovisual media on adolescents' knowledge about sexually transmitted infections in Seluma Regency. This research method is quantitative using a quasi-experimental approach (quasi-experiment) using a One Group Design Pretest-Posttest design. The sample in this study were 38 students of grade IX of SMPN 11, Seluma Regency. The sample selection method in this study used a purposive sampling method. The data collection technique used a questionnaire distributed to respondents before and after health education using audiovisual. The data obtained were then analyzed using a paired sample t-test. The results showed that the difference in the average value before and after health education using video was 1.26 with a p value = 0.001 with a significance level of 0.05. So it can be concluded that health education using audiovisual media can influence adolescents' knowledge about sexually transmitted infections. Therefore, the use of audiovisual media in conducting health education for students is highly recommended in order to create changes in adolescents' attitudes about Sexually Transmitted Infections (IMS).